Enhancing cloud data security using hybrid of advanced encryption standard and Blowfish encryption algorithms - -, Salma; Olanrewaju, Rashidah Funke; Abdullah, Khaizuran; -, Rusmala; Darwis, Herdianti (Institute of Electrical and Electronics Engineers Inc., 2019)
Cloud computing is an IT model that offers a large number of storage space, unbelievable computing power and inconceivable speed of calculations. There are a number of costumers like corporate components, social media programs and individual customers are all moving towards to the vast area of cloud computing. The importance of cloud computing comes out with the security of data accessibility, reliability and reliability of information. The verification and permission is more necessary to access information as 'cloud' is only assortment of actual super computer speed through the world. There are many research has been done on security of file encryption with AES algorithm. There is no any successful attack yet against AES but because of a higher increasing of cybercrime it could be possible attack on it like brute force attack and algebraic attack. Hence, in this research has been proposed a hybrid structure of Dynamic AES (DAES) and Blowfish algorithms. This procedure specifies the security of uploaded file on the cloud with a strong encryption method and also the privacy and reliability of submitted information of a user with considering performance of speed.